Boosting Health Campaign Reach and Engagement Through Use of Social Media Influencers and Memes. (May 2020) - Kostygina, Ganna; Tran, Hy; Binns, Steven; Szczypka, Glen; Emery, Sherry; Vallone, Donna; Hair, Elizabeth
Public health organizations are increasingly turning to social media as a channel for health campaign dissemination, as these platforms can provide access to "hidden" or at-risk audiences such as populations of color and youth. However, few studies systematically assess the effects of such campaigns in a competitive communication environment characterized by an influx of sophisticated tobacco product marketing. The objective of the current study is to investigate how content and source features of Twitter messages about truth ® campaigns influence their popularity, support, and reach. Keyword rules were used to collect tweets related to each of the six campaigns from the Twitter Firehose posted between August 2014 and June 2016. Data were analyzed using a combination of supervised and unsupervised machine learning, keyword algorithms, and human coding. Tweets were categorized by source type (direct or truth ® -owned social influencer; non-influencer). Tweet content was coded and classified for valence and campaign references (branded vs. non-branded or organic content). Message reach was calculated by source type and message type. Keyword filters captured 308, 216 tweets posted by 225, 912 Twitter users. Findings revealed that campaigns that utilized social influencers as message sources generated more campaign-branded and sharable content (e.g., campaign hashtags) and greater volume of tweets per day and reach per day. Influential users posted fewer organic messages and more branded/sharable content, generating greater reach compared to non-influencers. Oppositional messages decreased over time. Harnessing cultural elements endemic to social media, such as popular content creators (influencers) and messages (memes), is a promising strategy for improving health campaign interest and engagement.